2006
DOI: 10.1007/s10439-006-9177-6
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step 3-D Image Reconstruction in Magnetic Induction Tomography: Theoretical Limits of Spatial Resolution and Contrast to Noise Ratio

Abstract: Abstract-Magnetic induction tomography (MIT) is a lowresolution imaging modality for reconstructing the changes of the complex conductivity in an object. MIT is based on determining the perturbation of an alternating magnetic field, which is coupled from several excitation coils to the object. The conductivity distribution is reconstructed from the corresponding voltage changes induced in several receiver coils. Potential medical applications comprise the continuous, non-invasive monitoring of tissue alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…8,9 Some authors have indicated a desire to reduce the number of coils, with one approach calling for the repositioning of either the coils in the array or the object itself. 10 Whether MIT uses many or few coils, improved imaging calls for as many measurements as possible.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Some authors have indicated a desire to reduce the number of coils, with one approach calling for the repositioning of either the coils in the array or the object itself. 10 Whether MIT uses many or few coils, improved imaging calls for as many measurements as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Given the current iterate σ k , the step d needed to obtain the next iterate σ k+1 can be calculated by the regularized Gauss Newton method using the system of Equation (6). Alternatively, it can also be evaluated via the steepest descent method using (4), where the step factor α can be computed via the relation given by:…”
Section: Trust Region Powell's Dog Leg Methodsmentioning
confidence: 99%
“…To date, the major progress reported in MIT image reconstruction mainly involved the application of linear algorithms including single step schemes such as linear back-projection [3,4], Tikhonov regularization [5][6][7][8][9][10], truncated singular value decomposition (TSVD) [9], and iterative schemes like simultaneous iterative reconstruction technique (SIRT) [9], Landweber method [11] and the conjugate gradients least squares (CGLS) method [12]. Single step reconstruction methods are fast but they can only produce qualitative images.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic Tomography ( EMT ) is a noninvasive and contactless imaging modality based on law of electromagnetic induction, which aims to reconstruct the electrical conductivity distribution of the object field [1][2][3][4][5][6][7][8] .A sinusoidal time-varying magnetic field is generated by excitation coils and the changes within the object field due to conductivity perturbation are recorded by receiver coils. EMT, like EIT(electrical impedance tomography) and ECT (electrical capacitance tomography) is a 'soft-field' technique where the relation between measurements of receiver and conductivity distribution in object field is nonlinear, which can linear…”
Section: Introductionmentioning
confidence: 99%